Intertemporal and Social Preferences predict cooperation in a Social Dilemma: An application in the context of COVID-19 - M.A.J. van Hulsen; Kirsten I.M. Rohde; N.J.A. van Exel (Tinbergen Institute, 2020)
In this paper, we examine the role of intertemporal and social preferences in explaining cooperation in a social dilemma. In the Netherlands, the COVID-19 pandemic raised an acute social dilemma when the government opted for an “intelligent lockdown” to contain the spread of the virus, based on moral appeals and self-discipline rather than repression. Hence, citizens had to decide whether or not to comply with the precautionary measures recommended by the government. Through an online survey, using a general population sample of 1,019 adult citizens of the Netherlands, we measured people's consideration of future consequences (CFC), consideration of others (COO) and compliance with the precautionary measures recommended by the government. We find that both an increase in COO and an increase in CFC are associated with an increased compliance with the precautionary measures. Moreover, the marginal effects of COO and CFC are lower for higher values of CFC and COO, respectively. Overall, COO appears to have the largest influence on compliance. In addition to these two variables, gender, age, perceived risk for others, perceived compliance by others and opinion about government response to the pandemic had a significant effect on compliance. These findings emphasize the importance of both social as well as intertemporal preferences in the prediction of cooperation in social dilemmas.
Keywords: I18; D91; I12; 330; social preferences; time preferences; social dilemma; health; behavior; COVID-19